Pengaruh Asimetri Informasi, Manajemen Laba, dan Pengungkapan Intellectual Capital terhadap Cost of Equity Capital - Bela Laras Ati; Agus Afandi (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This research aims to examine the influence of information asymmetry, earnings management, and intellectual capital disclosure on the cost of equity capital in financial sector companies listed on the Indonesia Stock Exchange in 2019-2023. This research uses quantitative research and the data used in this research is secondary data in the form of annual reports for the 2019-2023 period. The number of samples used in this research was 50 from 10 companies in the population of financial sector companies. By using a purposive sampling method based on predetermined criteria. Based on the results of research that has been conducted, it shows that information asymmetry, earnings management, and Intellectual Capital disclosure have a simultaneous effect on the cost of equity capital. Information asymmetry and earnings management influence the cost of equity capital, while intellectual capital disclosure has no influence on the cost of equity capital.